2007
DOI: 10.1897/06-365r.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting metal uptake by wetland plants under aerobic and anaerobic conditions

Abstract: Metal pollution can be a serious threat to ecosystems at a global scale. Although the bioavailability of potentially toxic metals is determined by many biotic and abiotic factors, including pH and redox potential, total metal concentrations in the soil are used widely to assess or predict toxicity. In the present study we tested the effect of desiccation of soils differing in acidification potential and total heavy metal contamination on the growth and metal uptake of three typical, common wetland species: Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…pulex and A. aquaticus are 4.3 and 9.5 mg/L NH 3 –N, respectively. , The AC (as received and washed) was analyzed for total (aqua regia extractable) concentrations of heavy metals. , Concentrations of Cr, Cu, Ni, Zn, Pb, and As in AC were such that even at 30% AC the contribution of AC bound metals was less than 5% of the total concentration (Supporting Information, Table S2). This implies that metals did not interfere with treatment effects.…”
Section: Methodsmentioning
confidence: 99%
“…pulex and A. aquaticus are 4.3 and 9.5 mg/L NH 3 –N, respectively. , The AC (as received and washed) was analyzed for total (aqua regia extractable) concentrations of heavy metals. , Concentrations of Cr, Cu, Ni, Zn, Pb, and As in AC were such that even at 30% AC the contribution of AC bound metals was less than 5% of the total concentration (Supporting Information, Table S2). This implies that metals did not interfere with treatment effects.…”
Section: Methodsmentioning
confidence: 99%
“…Sufficient (i.e ., not limiting) food levels in general provide protection against metals toxicity (Heugens Environmental et al 2006). In soils as in freshwater (De Schamphelaere and Janssen 2006), pH is the major modifier of metals bioavailability (Kalis et al 2007;Vijver et al 2007) with modifications also resulting from dissolved organic matter (Amery et al 2007), but competing metal cations also play a role (Kalis et al 2006) as do biogeochemical changes due to both soil characteristics and plant-soil interactions (van der Welle et al 2007). Aging in terrestrial environments (processes by which the mobility and bioavailability of metals added to soil decline with time) reduces bioavailability of metals in general (Sauvé et al 2003); soils spiked with metal salts need to be leached prior to toxicity testing; otherwise toxicity will be overestimated (Oorts et al 2007).…”
Section: Factors Influencing Bioavailabilitymentioning
confidence: 99%
“…In turn, changes in soil pH influence the mobility, solubility and availability of micro-nutrients (Jacob and Otte, 2003; Kirk and Bajita, 1995; Luo et al, 2000; Mendelssohn, 1993; Youssef and Chino, 1991). Acidification associated with low pH enhances the plant’s ability to accumulate metals near the roots (Kirk and Bajita, 1995; Van der Welle et al, 2007). In the flooded treatment in the study reported here the change in pH near the roots was observed in the same zone of change in element concentrations (between the soil above the rhizoplane and the 6 mm interval).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests an important role of Fe in the underlying mechanisms of mobility of elements in the soil – Fe colloidal oxides are known to act as carriers of other metals (Shuman, 2005). Movement of iron as Fe(II) from the reduced soil layer to the oxidized soil above the rhizoplane most likely followed a concentration gradient caused by changes in Eh (De Laune et al, 1981; Neumann and Romheld, 2002; Van der Welle et al, 2007), while other elements behaved similarly because they are redox sensitive (Kirk, 2004) and/or they have a high affinity to co-precipitate or form complexes with secondary minerals of Fe (Kabata-Pendias and Pendias, 2001; Kirk, 2004; Mathys, 1980; Otte et al, 1991). In contrast, Ba has chemical properties similar to Ca and Sr (Suarez, 1996) and is usually associated with K in geochemical processes (Kabata-Pendias and Pendias, 2001).…”
Section: Discussionmentioning
confidence: 99%